Pemanfaatan AugmentedReality(AR) sebagai Media Promosi Iklan Produk Susu Kedelai Berbasis Filter Instagram - Sartika; Anung Rachman; Asmoro Nurhadi Panindias (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2021)
Augmented reality is a form of technology that combines the virtual world and the real world, and augmented reality is known as part of a virtual environment or virtual reality (VR) technology. AR can become a new promotional medium for the public or users. The purpose of this research is to develop or design an Instagram filter-based promotion with augmented reality (AR) technology to introduce soy milk products (sule). The design of this Instagram AR filter uses a design thinking approach according to the author in the process of designing an Instagram AR filter for this soy milk advertisement, this method is a method that may be quite relevant. The AR display when it becomes a filter on Instagram has several components, namely the main AR component, namely a 3D object image from soy milk product packaging.